STEM-BASED SOCIAL INTERACTION MODEL IN BUILDING COMMUNICATION RESIDENTS OF SOCIAL INSTITUTIONS ON BOGOR REGION - Nur Choiro Siregar; Dewi Anggrayni (Aksioma, 2023)
Social interaction based on science, technology, engineering, and mathematics (STEM) is one of the steps in building communication for each individual in facing the 4.0 era. Every student is required to have various skills, especially in the fields of science, technology, engineering, and mathematics. The objective of this study is to find out how the influence of STEM-based social interaction models in building communication for residents of the Azka Azkiya orphanage in the Bogor Region. The method in the study used a quasi-experimental pretest-posttest with nonequivalent groups and corroborated by the results of the interview. The respondents involved in the experiment were 24 students and in-depth interviews with two junior high school students. The result, based on the results of data analysis using independent t-test samples, found a value of t = -5.98; p < 0.05, meaning that there is an influence of STEM-based interaction models in improving students' communication skills. When the results of the thematic analysis were found, four themes showed good interaction with stem approaches, namely (1) interaction between students, (2) interaction between students-teachers, (3) interaction between student-content, and (4) interaction between student-environment. In conclusion, STEM-based learning processes can build student interaction and communication in their lives properly. In addition, it encourages students and teachers to be literate in science, technology, and engineering literacy in the face of the times. This research implies that STEM education needs to be included and made by education practitioners, namely teachers, and especially by the ministry of education into the curriculum in force in Indonesia. Future studies are necessary to conduct more samples from various regions in Indonesia to see the importance of STEM-based education is important to implement.